A study on policy proposals for expansion of solar photovoltaic system based on CBA and LCOE analysis in South Korea - Choi, Seungbong (KDI School, 2018)
Korean government set the target to boost the proportion of renewable energy in power generation to 20 percent by 2030 by replacing 57.3% of renewable energy with solar PV. In order to expand the usage of renewable energy, government has spread various energy policies. However, in the process of spreading various policies to expand solar PV, there have been unexpected inverse effects such as devastation of forest by the expansion of solar PV in forest. This study conducted CBA and LCOE analysis of 1MW utility scale solar PV by taking all possible cases into consideration such as solar radiation and land lease costs which differs by region in South Korea in order to minimize the unexpected adverse effects and expand solar PV effectively. Then, this study gave policy proposals to expand solar PV based on this analysis. It is expected that the results contribute to right decision making process regarding expansion of solar PV. Also, these results can help policymakers to improve the existing solar PV associated with policies and accelerate industrial key players to invest solar PV. Ultimately, it is expected that this study contribute to reducing the burden of electricity rates on people resulting from government's expansion of solar PV.
Thesis(Master) --KDI School:Master of Public Management,2018.